HYDRODYNAMIC-WAVE CALIBRATION OF POTENTIALS IN MAXWELL'S EQUATIONS: NON-LINEAR DYNAMICS AND COHERENCE, COLLAPSE, EXPANSION AND EXCHANGE INTERACTION OF INERTIAL DISSIPATIVE-COLLECTOR DISTURBANCES IN NON-EQUILIBRIUM MEDIA IN THE COMPLEX SPACE. SPIRAL TURBULENCE AND COHERENT STRUCTURES OF THREE-DIMENSIONAL TIME - ZASPA, Yurii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The results of the hydrodynamic-wave calibration of the potentials in Maxwell's equations and their analogs for the gravitational field, which combine Euler's hydrodynamics, Maxwell's electrodynamics, and d'Alembert's wave apparatus with quantum principles, are given. The nonlinearity of the equations for the vector-potential with the velocity dimension ensures the interrelationship of different field forms and the cascade transport of energy by the disturbance spectrum. The obtained solutions of these equations for inertial dissipative-collector disturbances, which are characterized by a balance of local and convective acceleration, and also balance local dissipation (accumulation) with local metainertia. The vector-potential (wave function) of such forms includes a complex Euler exponent, the phase of which depends on the coordinates of the disturbances paired in the complex space - without distinguishing its real or imaginary half. Reasoned constancy of the phase, which ensures the coherent nature of the propagation of running field forms in complex space, as well as in topologically adequate three-dimensional time. The latter is considered in a cylindrical coordinate system that combines spiral and jet time forms. The correspondence of the components to the Laplace operator (in the spherical spatial coordinate system associated with the pair of disturbances) with respect to the near-acting centrifugal energy of repulsion and the long-range exchange energy of attraction, which collectively provide the mechanisms of collapse, expansion, and dynamic balance of the pair, has been revealed. Coherent resonant forms of motion with a three-dimensional topology of time are highlighted, which are widely represented, in particular, on the spectra of collider resonances, as well as on the spectra of technical, hydrodynamic, geophysical, and space turbulence. It is noted that such turbulence is described precisely by Maxwell's equations in the hydrodynamic-wave calibration of potentials, and not by the Navier-Stokes equations, or by the truncated equations of magnetohydrodynamics, which completely ignore the displacement current in Maxwell's equations. The obtained calculation results are confirmed by actual data in the systems of different levels of the organization. The main role of inertial dissipative-collector disturbances in the processes of dynamic thermoregulation of the Earth's climate during the cyclical change of climatic optimums during ice ages has been established. In this context, criticism of the current noisy concepts of global warming, which exaggerate anthropogenic  factors without taking into account the dominant natural factors, is presented. It is indicated that these factors should be considered in an expanded format of complex space and three-dimensional time without artificial constructions and self-limitations inherent, in particular, in modern standard physical models Lambda-CDM and SM.
Keywords: Maxwell's equations; hydrodynamic-wave calibration of potentials; complex space; nonequilibrium system; inertia; metainertia; dissipation; accumulation; phase; coherence; resonances; three-dimensional time